Dietary effects of Coriandrum sativum extract on growth performance, physiological and innate immune responses and resistance of rainbow trout (Oncorhynchus mykiss) against Yersinia ruckeri - Mehdi Naderi Farsani (2019)
© 2019 Elsevier Ltd This investigation was aimed to determine the efficacy of coriander seed extract (Coriandrum sativum) on physiological responses, immunity and disease resistance of rainbow trout, Oncorhynchus mykiss for eight weeks. A total number of six hundred rainbow trout (62 ± 0.81 g) were divided into four feeding groups including 0 (control), 0.5%, 1% and 2% of coriander seed extract (CSE). In the present study, rainbow trout fed with 2% of CSE showed significantly higher values of specific growth rate (SGR), final weight (FW) and condition factor (CF) in comparison with control group after eight weeks (P < 0.05). Regarding hematological indices results, the 2% dosage of CSE showed the highest amount of hematocrit and hemoglobin compared to control group (P < 0.05). In addition, significant improvement of lysozyme and alternative complement activity, were observed in 2% of CSE treatment (P < 0.05). After eight weeks post-feeding, 30 fish from each treatment were challenged with Yersinia ruckeri for 14 days. The findings presented that fish fed with CES, especially 2% of CSE inclusion, improved survival rate of rainbow trout against Y. ruckeri; however, there were no significant differences among the fish in control and treatment groups at the end of the eight weeks feeding with coriander seed extract. The present study demonstrated, dietary incorporation of coriander extract can improve growth factors, immunological indices and resistance of rainbow trout (O. mykiss) against Y. ruckeri infection.